A Review Of Notary Positions: Submission Of Notary Proto-cols Aged 25 Years Or More In Medan City - Yosua Leo Ezra Roito Simamora; Hasim Purba; Suprayitno, Suprayitno (Jurnal Ekonomi, 2024)
The storage of Notary Protocols that are not submitted by Notaries to the Regional Supervisory Board is not in accordance with the provisions in Article 63 paragraph (5) of the UUJN, that Notary protocols that have exceeded a period of 25 (twenty five) years or more must be submitted to the Regional Supervisory Board. This paper discussed a formulation of the problem in this study is responsibility of notaries for notary protocols that are 25 years old or more and the application of Article 63 paragraph (5) of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notaries in the process of submitting notary protocols; also impact on notaries who do not submit notary protocols that are 25 years old or more as regulated in Article 63 paragraph (5) of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notaries. This study uses an empirical legal method with a statutory and conceptual approach. Data were obtained from interviews with notaries in Medan City, as well as legal document studies. The analysis was conducted qualitatively with the aim of examining notary protocol issues, combining legal theory with field data, and drawing deductive conclusions. The results of the study found that notary protocols that are 25 years old or more are regulated in Article 63 paragraph (5) of the UUJN which requires notary protocols to be submitted to the MPD in accordance with the authority of the MPD in Article 70 letter e of the UUJN, where in its implementation it is carried out through an inventory mechanism, making a list of protocols and minutes of handover, but is constrained by limited storage space, damaged protocol conditions, incomplete documents and lack of coordination, so that if the notary does not submit the protocol, administrative sanctions can be imposed in accordance with Article 85 of the UUJN in the form of verbal or written warnings, temporary dismissal, honorable or dishonorable dismissal which can affect the credibility and professionalism of the notary.